Effects of deep vertical rotary tillage on the grain yield and resource use efficiency of winter wheat in the Huang-Huai-Hai Plain of China - Fen WU; Li-chao ZHAI; Ping XU; Zheng-bin ZHANG; Elamin Hafiz BAILLO; Lemessa Negasa TOLOSA; Roy Njoroge KIMOTHO; Xiu-ling JIA; Hai-qian GUO (Journal of Integrative Agriculture, 2021)
Tillage represents an important practice that is used to dynamically regulate soil properties, and affects the grain production process and resource use efficiency of crops. The objectives of this 3-year field study carried out in the Huang-Huai-Hai (HHH) Plain of China were to compare the effects of a new deep vertical rotary tillage (DVRT) with the conventional shallow rotary tillage (CT) on soil properties, winter wheat (Triticum aestivum L.) grain yield and water and nitrogen use efficiency at different productivity levels, and to identify a comprehensive management that optimizes both grain yield and resource use efficiency in the HHH Plain. A split-plot design was adopted in field experiments in the winter wheat growing seasons of 2016–2017 (S1), 2017–2018 (S2) and 2018–2019 (S3), with DVRT (conducted once in June 2016) and CT performed in the main plots. Subplots were treated with one of four targeted productivity level treatments (SH, the super high productivity level; HH, the high productivity and high efficiency productivity level; FP, the farmer productivity level; ISP, the inherent soil productivity level). The results showed that the soil bulk density was reduced and the soil water content at the anthesis stage was increased in all three years, which were due to the significant effects of DVRT. Compared with CT, grain yields, partial factor productivity of nitrogen (PFPN), and water use efficiency (WUE) under DVRT were increased by 22.0, 14.5 and 19.0%. Path analysis and direct correlation decomposition uncovered that grain yield variation of winter wheat was mostly contributed by the spike numbers per area under different tillage modes. General line model analysis revealed that tillage mode played a significant role on grain yield, PFPN and WUE not only as a single factor, but also along with other factors (year and productivity level) in interaction manners. In addition, PFPN and WUE were the highest in HH under DVRT in all three growth seasons. These results provided a theoretical basis and technical support for coordinating the high yield with high resource use efficiency of winter wheat in the resource-restricted region in the HHH Plain of China.